Serbs in the Petrinja district - historiographical and ethnographic overview (part II) - Škiljan Filip (Glasnik Etnografskog Instituta SANU)
The author in the text, based on archival material, literature and narrator’s testimony, provides information about the elements of the national identity of the Serbs of the Petrinja region. In particular, it deals with the Orthodox religion and the narrator’s memories of everyday life during socialism, the last war (1991-1995) and the nowadays. The text also provides demographic data of Serbs population in the Petrin region.